Implementasi Nilai-Nilai Pendidikan Agama Islam di Era Modern - Kevin Maulana Al Ghafar; Muhammad Oriza Pradana; Izzul Nurdin Setyawan (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
The transformation of Islamic Religious Education (PAI) in the digital era is currently confronted with multifaceted challenges, primarily the escalation of moral degradation and identity crises triggered by the pervasive integration of technology and Artificial Intelligence (AI). This study aims to critically analyze and formulate strategic frameworks for implementing PAI values that remain adaptive to modern demands while preserving the ontological essence of spirituality and character integrity. Employing a Systematic Literature Review (SLR) methodology, this research synthesized 20 high-quality scientific articles published within the last five years to ensure data actuality and relevance. The analysis proposes a "Synthesis Model" that bridges the gap between traditional Islamic pedagogical ethics and contemporary technological disruptions through a systemic approach involving input, process, and output components. The findings reveal that effective transformation is achieved through the reorientation of the curriculum toward a holistic-integrative model, where ethics-based digital literacy is organically merged with core theological subjects. Furthermore, technology is repositioned as a wasilah (strategic medium) to strengthen spiritual connections rather than a mere administrative tool. This study concludes that the future of Islamic education depends on its capacity to maintain a precise equilibrium between technological functionalism and spiritual depth, ultimately cultivating a generation that is digitally proficient, morally resilient, and capable of demonstrating religious moderation in a globalized society. This integration of values, specifically by adopting universal Quranic principles as social solutions, serves as a crucial foundation for the realization of the insan kamil who is resilient in facing the currents of globalization.